Ketidakmampuan Membaca (Disleksia) dan Dampaknya Terhadap Perkembangan Anak - Fika Safitri; Faris Naufal Ali; Eva Latipah (PGSD Universitas Muria Kudus, 2022)
The purpose of this study was to identify dyslexia disorders, and how to apply and treat them, so that they can help and reduce the impact of subsequent development. This research uses library research and the type of research is descriptive qualitative analysis. The data collection method is from the book